PENGEMBANGAN MEDIA KADO (KARTU DOMINO) DENGAN BARCODE MATERI SEJARAH KEMERDEKAAN DIKELAS VI SD - Ilham Juniardi; Maharani Oktavia; Puji Ayu Rachamawati (Jurnal DIDIKA: Wahana Ilmiah Pendidikan Dasar, 2023)
This research aims to produce KADO media (domino card) with barcode in social studies learning material on the history of independence in class VI elementary school that is valid and practical. The type of research used is research and development with the ADDIE model with five stages, namely: Analyze, Design, Development, Implementation and Evaluation. The research subjects were class VI students at SD Negeri 3 Rambutan. The results of this research show that KADO media (domino card) with barcode on the history of independence in class VI elementary school are in the very valid category, namely 86,9% of the combined results of the three validators. Furthermore, in the one to one trial stage carried out by 3 students reached 92.6%, the small group trial involving 8 students reached 93.7% and the results of the large group trial involving 20 students reached 94.9%. It can be said that these three stages are very practical, so it can be concluded that KADO media (domino card) with barcode on the history of independence material are suitable for use. Keywords : Development, History of independence, Dominoes